Flexible Takagi-Sugeno fuzzy systems - Cpalka, K.; Rutkowski, L. (Proceedings. 2005 IEEE International Joint Conference on Neural Networks, 2005, 2005)
In the paper, a new class of Takagi-Sugeno fuzzy systems is derived. Various parameters and weights are incorporated into construction of such systems. The approach presented in the paper introduces more flexibility to the structure and design of neuro-fuzzy systems.